2013
DOI: 10.1371/journal.pone.0074875
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide Corrects the Imbalance between Omega-6 to Omega-3 Polyunsaturated Fatty Acids and Inhibits Macrophage Inflammatory Mediators via the ERK Pathway

Abstract: We previously identified Fragile X-related protein 1 (FXR1) as an RNA-binding protein involved in the post-transcriptional control of TNF and other cytokines in macrophages. Macrophages derived from FXR1-KO mice overexpress several inflammatory cytokines including TNF. Recently, we showed that fenretinide (4HPR) is able to inhibit several inflammatory cytokines in the lungs of cystic fibrosis mice, which also have abnormal immune responses. Therefore, we hypothesized that 4HPR might also be able to downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…We and others previously showed that ERK1/2 MAPK is activated following infection by S. suis (27,31). We have also previously demonstrated that fenretinide is able to downregulate ERK1/2 phosphorylation in LPS-treated macrophages (32). In the present study, macrophages pretreated with fenretinide prior to S. suis infection showed a significant reduction in ERK1/2 activation compared to nontreated S. suis-infected macrophages (Fig.…”
Section: Fenretinide Attenuates Erk Mapk and Cox-2 Activation In Murisupporting
confidence: 81%
“…We and others previously showed that ERK1/2 MAPK is activated following infection by S. suis (27,31). We have also previously demonstrated that fenretinide is able to downregulate ERK1/2 phosphorylation in LPS-treated macrophages (32). In the present study, macrophages pretreated with fenretinide prior to S. suis infection showed a significant reduction in ERK1/2 activation compared to nontreated S. suis-infected macrophages (Fig.…”
Section: Fenretinide Attenuates Erk Mapk and Cox-2 Activation In Murisupporting
confidence: 81%
“…Our studies clearly demonstrate that treatment of allergen-sensitized and allergenchallenged mice with LAU-7b had lower expression of Il-4 (WT mice), Il-5 and Eotaxin-1 (WT and KO mice) compared to PBS-treated mice which is consistent with the previously reported effect on ERK1/2 phosphorylation (Lachance et al 2013). IL-13 is a key regulatory cytokine in the production of IgE (Rael et al 2011).…”
Section: Downloaded Fromsupporting
confidence: 92%
“…For the glucose tolerance test, after 10 weeks of treatment, mice were fasted for 5 hr and then injected with 2 g·kg −1 glucose via intraperitoneal injection of 20% w/v sterile glucose solution in PBS. Glucose levels were determined as described previously (Lachance et al, ).…”
Section: Methodsmentioning
confidence: 99%